Nigerian School Teachers' Perception of Students' Use of Basic Mathematical Knowledge and Skills in Reading, Preparing and Interpreting Football League Table - Idehen, Festus; Oteze, Kate I. (NIU Journal of Social Sciences; Vol 6 No 3 (2020): KIU Journal of Social Sciences, Vol. 6 No. 3, September 2020, 2020)
This study assessed the perception of secondary school teachers of their students' use of basic mathematical knowledge and skills in reading, preparing and interpreting football league tables. The descriptive survey research design was employed to select a total of 108 teachers from 25 schools across Edo and Delta states of Nigeria. The instrument for the study was a 4-point Likert scale on needed students' Basic mathematical knowledge and Skills (BMKS) in reading, preparing and interpreting football league table. The BMKS was validated and with a Cronbach-Apha reliability coefficient of 0.838 estimate. Means and t-test statistic were used to analyze data and answer the research questions and test the hypothesis. The findings showed that the teachers perceived that basic mathematical knowledge and skills such as counting, addition, subtraction, multiplication, division, and ordering of numbers are needed by students to read, prepare and interpret football league table. The findings also showed that seven mathematical knowledge and skills within four statistical thinking levels are highly used by students to prepare football league table. To connect classroom mathematics to students’ daily experience and social lives, Nigerian teachers are encouraged to have the right perception of their students’ mathematical knowledge and skills dispositions through personal assessment. Key Words: Teachers' Perception, Students' use, Mathematical Knowledge and Skills, Statistical Thinking Levels, Preparation of Football League Table